Low viral predation pressure in cold hypersaline Arctic sediments and limits on lytic replication. Issue 2 (23rd February 2016) - Colangelo‐Lillis, Jesse; Wing, Boswell A.; Whyte, Lyle G.
Summary: Viruses are ubiquitous drivers of microbial ecology and evolution and contribute to biogeochemical cycling. Attention to these attributes has been more substantial for marine viruses than viruses of other environments. Microscopy‐based investigation of the viral communities from two cold, hypersaline Arctic springs was undertaken to explore the effects of these conditions on microbe–viral ecology. Sediments and water samples were collected along transects from each spring, from anoxic spring outlets through oxygenated downstream channels. Viral abundance, virus–microbe ratios and modelled virus–microbe contact rates were lower than comparable aqueous and sedimentary environments and most similar to deep subsurface sediments. No individual cell from either spring was visibly infected. Viruses in these springs appear to play a smaller role in controlling microbial populations through lytic activity than in marine water column or surface sedimentary environments. Relief from viral predation indicates the microbial communities are primarily controlled by nutrient limitation. The similarity of these springs to deep subsurface sediments suggests a biogeographic divide in viral replication strategy in marine sediments.